2016
DOI: 10.1097/bor.0000000000000256
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and osteoarthritis

Abstract: These new findings open the way to better understand the bone subtypes of osteoarthritis (osteoporotic, bone forming and erosive) and the common and different ways bone is involved in osteoporosis and osteoarthritis. Much can be expected from further prospective studies, when taking into account the heterogeneous nature of both osteoporosis and osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 49 publications
0
36
0
2
Order By: Relevance
“…Except for the small sample size, a plausible scenario could be in the follows. OA is an age strongly-related degenerative disease, and BMI has opposing effect on OA and OP; also, local in ammation caused by mechanical injury, rather than systemic one caused by autoimmunology, is its salient feature 36 . Whether pSS would gain higher prevalence of OP or osteopenia is still uncertain 12 and in present study were mostly in early-onset and untreated.…”
Section: Prevalence Of Bone Loss and Odd Ratiosmentioning
confidence: 99%
“…Except for the small sample size, a plausible scenario could be in the follows. OA is an age strongly-related degenerative disease, and BMI has opposing effect on OA and OP; also, local in ammation caused by mechanical injury, rather than systemic one caused by autoimmunology, is its salient feature 36 . Whether pSS would gain higher prevalence of OP or osteopenia is still uncertain 12 and in present study were mostly in early-onset and untreated.…”
Section: Prevalence Of Bone Loss and Odd Ratiosmentioning
confidence: 99%
“…1 Hazard ratio for femur neck and trochanteric fracture before and after total knee replacement (TKR), adjusted for age, gender, calendar year, and latitude Table 3 The hazard ratios (with 95% CI) for hip fracture before and after total knee replacement (TKR), according to age, compared to individuals without TKR [25]. Women and men with osteoarthritis tend to have a higher BMI [11,13]. Obese individuals tend to have increased BMD but are also associated with a lower rate of bone formation [10].…”
Section: Bmd Bmi Falls and Fracturementioning
confidence: 99%
“…Several studies have reported an association between high bone mineral density (BMD) and osteoarthritis [10]. In contrast, other reports infer that both women and men with osteoarthritis also may have osteoporosis or osteopenia [11,12] and an increased risk of falls and fracture [10,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…It affects about one third of women and one fifth of men aged 50 years and older in the United States 45 . Although osteoarthritis and osteoporosis are traditionally viewed to have an inverse relationship 46 , contemporary understanding of both diseases recognize different disease phenotypes, including the presence of osteoporotic, erosive and bone-forming osteoarthritis phenotypes 4649 . Indeed, several studies found a high prevalence of osteoporosis in THA and TKA patients 5053 .…”
Section: Comorbiditiesmentioning
confidence: 99%